Implementasi Tahap Enaktif-Ikonik-Simbolik (EIS) Bruner untuk Meningkatkan Pemahaman Konsep Operasi Perkalian pada Siswa Sekolah Dasar: Studi Literatur Tingkat Dasar - Suci Aulia Safira; Sahwa Anisa; Nurul Habibah; Tiara Desky; Misrina Misrina (Universitas Ma'arif Lampung, 2025)
This study aims to describe Jerome S. Bruner's learning theory and its developmental stages in depth, and to explain the application of each stage in helping students understand basic concepts of Mathematics, especially in the material of multiplication operations at the elementary school level. The problem in this study is since many elementary school students still consider Mathematics as a difficult, confusing, and less enjoyable subject. This is caused by the learning process, which is monotonous, abstract, and does not pay attention to the characteristics and stages of cognitive development of students who are still in the concrete operational phase. This study uses a descriptive qualitative method with a literature review approach to various relevant sources such as books, scientific articles, and research journals that discuss Bruner's theory and its application in Mathematics learning. The results of the study show that the application of Bruner's three stages of mental representation, namely the enactive, iconic, and symbolic stages, can help students understand the meaning, structure, and concept of multiplication operations gradually. Thus, learning becomes more meaningful, active, interesting, contextual, and in accordance with the cognitive development of elementary school students.